Chondrosarcoma of bone in children and adolescents. (2020) - Kaneuchi, Yoichi; Fujiwara, Tomohiro; Tsuda, Yusuke; Yoshida, Shinichirou; Stevenson, Jonathan D.; Abudu, Adesegun
Abstract: Purpose: Chondrosarcomas typically present in adults during the fifth to seventh decades and are rare in young patients. The biological behaviour and oncological outcomes may be different in children and adolescents. Methods: We retrospectively evaluated the outcomes of all patients with chondrosarcoma of bone who were younger than 18 years of age at the time of diagnosis and were treated at our centre between 1995 and 2018. Results: The 15 consecutive patients studied included nine male and six female cases, with a mean age at diagnosis of 13 years (7 to 17). The median follow-up was 117 months (30 to 277). The tumours were primary and secondary in ten and five patients, respectively. The tumours were central in 13 and surface in two patients. The tumour locations were the humerus in five, digits in five, femur in three, radius in one and pelvis in one patient. The histological grades were grade I in seven, grade II in seven and grade III in one patient. The surgical treatments were limb salvage in ten patients and ray amputation in five patients. The surgical margins were wide in eight, marginal in two and intralesional in five patients. All the patients were alive and continuously free of disease at the time of the last follow-up. No patient developed metastases or local recurrence. Conclusion: Chondrosarcoma of bone in children and adolescent patients has a very good prognosis and is less aggressive compared with published outcomes in older patients. Level of evidence: IV